Integrating Psychological Resilience, Stress, and Coping in Entrepreneurship: A Critical Review and Research Agenda - Ahmed, Ali E.; Ucbasaran, Deniz; Cacciotti, Gabriella; Williams, Trenton A. (Entrepreneurship Theory and Practice, 2022)
Despite the increasing interest in studying the concept of resilience in entrepreneurship, existing research often fails to account for stressors that induce entrepreneurs’ need for resilience and coping efforts. By arguing the need to study stress, resilience, and coping together to understand how entrepreneurs build resilience in the face of adversities, we systematically review the entrepreneurship scholarship (125 articles) on these three concepts. By critically appraising these three literatures in light of current thinking in psychology, we then develop a model of the process of building psychological resilience in entrepreneurship and offer a clear pathway for future research.